2005
DOI: 10.1038/sj.jp.7211410
|View full text |Cite
|
Sign up to set email alerts
|

A study of the role of multiple site blood cultures in the evaluation of neonatal sepsis

Abstract: Background: The optimal number of blood cultures needed to document sepsis in an ill neonate has undergone little critical evaluation. Multiple site cultures may improve pathogen detection if intermittent bacteremia occurs, or if a low density of bacteria is present in the blood. We hypothesized, however, that bacterial clearance is slower and bacteremia more continuous in septic neonates, so that a single site blood culture should be sufficient to accurately document true septicemia.Objective: To determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 20 publications
2
48
1
7
Order By: Relevance
“…We have shown previously that a single-site blood culture should be sufficient to document sepsis in symptomatic infants, and is biologically plausible because young infants have high-colony-count bacteremia, the bacterial clearance is slower and the bacteremia more continuous in newborns with sepsis than in older patients. 16 The distribution of pathogens causing sepsis in a specific hospital unit is usually considered when empiric antibiotics are selected, but 'this approach assumes that all pathogens causing sepsis have equal likelihood of causing severe complications including meningitis and death,' 17,18 and that all antibiotics will have good cerebrospinal fluid penetration and be equally effective to treat meningitis, which is commonly associated with Gram-negative sepsis. In reality, when empiric antibiotics for late-onset sepsis are selected, one should be especially concerned about fulminant late-onset Gram-negative sepsis, in which infants die before pathogens and antibiotic susceptibilities have been identified, often in <48 h of onset of illness.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown previously that a single-site blood culture should be sufficient to document sepsis in symptomatic infants, and is biologically plausible because young infants have high-colony-count bacteremia, the bacterial clearance is slower and the bacteremia more continuous in newborns with sepsis than in older patients. 16 The distribution of pathogens causing sepsis in a specific hospital unit is usually considered when empiric antibiotics are selected, but 'this approach assumes that all pathogens causing sepsis have equal likelihood of causing severe complications including meningitis and death,' 17,18 and that all antibiotics will have good cerebrospinal fluid penetration and be equally effective to treat meningitis, which is commonly associated with Gram-negative sepsis. In reality, when empiric antibiotics for late-onset sepsis are selected, one should be especially concerned about fulminant late-onset Gram-negative sepsis, in which infants die before pathogens and antibiotic susceptibilities have been identified, often in <48 h of onset of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the optimal number of blood cultures and the ideal volume of blood needed to detect neonatal bacteremia are a matter of ongoing debate [27,28]. Multiple BC collection is especially problematic in neonates and often only one culture is (or can be) obtained [29]. Efforts have been made to enforce the clinical use of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Indications for the diagnostic blood cultures and the results of that study have been previously reported. 3 When diagnostic cultures were reported to be positive then central lines were removed, initial empiric antimicrobial therapy was altered according to the susceptibility of the isolate, and optimal antimicrobial drug concentrations were monitored. Details of the blood culture collection and skin cleansing methods have been summarized elsewhere.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the blood culture collection and skin cleansing methods have been summarized elsewhere. 3 At the discretion of the attending neonatologist, beginning 48 to 72 h after initiation of antimicrobial therapy, follow-up blood cultures were drawn from two different peripheral sites with a minimum of 1.0 ml of blood from each site. Repeat cultures were obtained every 24 to 48 h until both blood cultures became negative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation